Pengabdian Kepada Masyarakat Workshop Canva: Meningkatkan Kualitas Pemasaran Produk Lokal UMKM di Piru, Kabupaten Seram Bagian Barat - Souisa, Wendy; Lussy, Kalsum; Pandu, Imanuela; Nahuway, Victorio F. (JURNAL PENGABDIAN MASYARAKAT JAMAK, 2023)
This workshop aims to equip Micro, Small, and Medium Enterprises (MSMEs) in Piru, West Seram Regency, with skills to use Canva to improve the marketing quality of their local products. Canva is an easy-to-use graphic design platform, allowing MSMEs to create attractive and professional promotional materials without needing a deep design background. This Canva workshop is designed to produce concrete and measurable outputs, which not only demonstrate the success of the training but also provide direct added value to participants and relevant parties. Through this combination of evaluation methods, the workshop organizers can gain a comprehensive overview of the training's impact, identify areas of success, and find room for improvement for better MSME empowerment programs in Piru, West Seram Regency.Keywords: Canva Workshop, Marketing Quality